2001
DOI: 10.1034/j.1399-3038.2001.0o057.x
|View full text |Cite
|
Sign up to set email alerts
|

Cow's milk protein intolerance and chronic constipation in children

Abstract: Cow's milk protein (CMP) allergy was investigated in 25 children (age-range 3 months to 11 years) with chronic constipation. A diagnosis of constipation was made on the basis of a history of painful elimination of hard stools for at least 1 month, whether or not associated with a reduced frequency of stools or soiling. The children were evaluated using clinical parameters and the following laboratory tests: total serum immunoglobulin E (IgE); specific IgE (radioallergosorbent test [RAST]) for whole cow's milk,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 11 publications
2
72
0
4
Order By: Relevance
“…Although our and others' studies have shown the relationship between cows' milk protein intolerance (CMPI) and chronic constipation [3][4][5][11][12][13], very little is known about the pathogenesis of chronic constipation caused by CMPI. Consequently, we performed this study Table 3 Anorectal manometry results in patients with food intolerance-related chronic constipation at entry to the study and after 12 weeks of elimination diet, and in patients with chronic constipation not related to food intolerance…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our and others' studies have shown the relationship between cows' milk protein intolerance (CMPI) and chronic constipation [3][4][5][11][12][13], very little is known about the pathogenesis of chronic constipation caused by CMPI. Consequently, we performed this study Table 3 Anorectal manometry results in patients with food intolerance-related chronic constipation at entry to the study and after 12 weeks of elimination diet, and in patients with chronic constipation not related to food intolerance…”
Section: Discussionmentioning
confidence: 99%
“…According to the European Society Pediatric Gastroenterology Hepatology and Nutrition diagnostic criteria for food intolerance/allergy [14], we can affirm that half of the patients included in the study (17 out of 36) were suffering from food intolerance that caused chronic constipation. As studies from other centres showed a frequency of constipation caused by CMI ranging between 28 and 70% [11][12][13], it can be concluded that in patients unresponsive to conventional treatments or with a personal history of CMI, constipation is quite frequently a manifestation of food intolerance.…”
Section: Figmentioning
confidence: 99%
“…Outro aspecto relaciona-se com a boa digestibilidade dos lipídeos do leite humano em relação às fórmulas, o que favorece a formação de fezes menos consistentes 22 . Após o desmame, alguns casos de constipação podem ser atribuí-dos à intolerância ou alergia à proteína do leite de vaca [23][24][25] . Acrescentando-se essas evidências fisiológicas 20,21 e patológicas [21][22][23] aos resultados do nosso estudo, o aleitamento natural deve ser considerado como um fator de proteção contra o desenvolvimento de constipação.…”
Section: Discussionunclassified
“…Nas seis crianças que realizaram biópsia retal observou-se infiltrado de eosinófilos na lâmina pró-pria. Outro estudo 48 foi realizado em São Paulo. Dieta sem leite de vaca foi recomendada para 40 pacientes com constipação atendidos em ambulatório especializado.…”
Section: Diagnóstico Diferencialunclassified